Twenty Years in Prison: Reflections on Conducting Research in Correctional Environments - Field, Courtney (The prison journal, 2019)
Prisons are a difficult terrain in which to undertake research. Our experience in conducting a comprehensive prevalence study of health factors across New South Wales has provided us with a unique perspective on how to overcome common difficulties when undertaking prison-based research that may otherwise seem insurmountable. We outline six domains that constitute major challenges to the successful completion of projects as we understand them and offer practical solutions where possible. Our aim is to encourage researchers to undertake this important work in a manner that will provide positive outcomes for researchers, organizations working in the corrections space, and inmates.